Freelance '90 - Weibull, Lennart (University of Gothenburg, 1991)
The main purpose of this survey was to study the group of journalists who earn a living working as freelancer. Questions were asked about age, sex, marital status, housing, family size and composition, place of living, education and income. Other questions delt with ideological aspects on freelance work, the reason why one worked as a freelancer, and if it is easier or more difficult to fulfil certain criteria associated with the journalist rôle. How and to whom one sells material. What kind of material one sells, and if this is what one wants to produce. The position of freelancer on a political left-right scale and a scale measuring the green dimension, i.e. interest in environmental questions.

Undersökningens syfte var att kartlägga den grupp journalister som försörjer sig som frilansare. Enkäten tog upp demografiska frågor såsom ålder, kön, civilstånd, bostadstyp, hushållets storlek och sammansättning, bostadsort, utbildning och inkomst. Andra frågor berörde ideologiska aspekter på frilansarbete. Varför man arbetar som frilans och hur man ser på arbetet, om det är lättare eller svårare att som frilans uppfylla vissa kriterier som förknippas med journalistrollen. Hur säljer man sitt material och till vem, vilken typ av material säljer man och överensstämmer detta med det man vill producera. Därutöver ställs frågor om frilanskårens placering på en vänster-högerskala samt placeringen längs en skala som mäter den gröna dimensionen, dvs intresset för miljöfrågor.
Frilans '90
Keywords: Media; Media; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap